Analgesic Effect of Intra-Articular Injection of Temperature-Responsive Hydrogel Containing Bupivacaine on Osteoarthritic Pain in Rats. (31st December 2015) - Kim, Taemin; Seol, Dong Rim; Hahm, Suk-Chan; Ko, Cheolwoong; Kim, Eun-Hye; Chun, Keyoungjin; Kim, Junesun; Lim, Tae-Hong
Abstract : The present study examined the analgesic effects of slow-releasing bupivacaine from hydrogel on chronic arthritic pain in rats. Osteoarthritis (OA) was induced by monosodium iodoacetate (MIA) injection into the right knee joint. Hydrogel (HG: 20, 30, and 50  μ L) and temperature-sensitive hydrogel containing bupivacaine (T-gel: 20, 30, and 50  μ L) were injected intra-articularly 14 days after MIA injection. Behavioral tests were conducted. The rats showed a significant decrease in weight load and paw withdrawal threshold (PWT). Intra-articular 0.5% bupivacaine (10 and 20  μ L) significantly reversed MIA-induced decreased PWT, with no effect on weight load. In normal rats, hydrogel did not produce significant changes in PWT but at 30 and 50  μ L slightly decreased weight bearing; T-gel did not cause any changes in both the weight load and PWT. In OA rats, T-gel at 20  μ L had a significant analgesic effect for 2 days, even though T-gel at 50  μ L further reduced the weight load, demonstrating that intra-articular T-gel (20  μ L) has long-lasting analgesic effects in OA rats. Thus, T-gel designed to deliver analgesics into the joint cavity could be an effective therapeutic tool in the clinical setting.